(untitled) (Annals of Medical Research, 2021)
Aim: Although antibiotics are generally well-tolerated, they may have cytotoxic effects. The present randomized, double-blind, in vitro study aimed to investigate the effects of tigecycline on cartilage tissue cells and the extracellular matrix.Material and Methods: Cartilage tissues of patients (n = 8) were used for the preparation of primary cell cultures. Tigecycline-treated cell cultures served as the study group. Non-treated cell cultures served as the control group. Analyses were performed at 0, 24, 48, and 72 h in both groups. The results obtained were statistically evaluated. The alpha significance value was determined to be 0.05.Results: Proliferation remained unchanged in the tigecycline-treated cell cultures. The gene expressions of the markers involved in anabolic pathways increased in the tigecycline-treated cell cultures. The results obtained were statistically significant (P 0.05). Conclusion: Although tigecycline had no toxic effect on the chondrocyte cell cultures and caused no damage to the extracellular matrix, the present study was performed in an in vitro environment.